Bayesian optimization of the composition of the lanthanide metal–organic framework MIL-103 for white-light emission. Issue 4 (28th February 2023) - Kitamura, Yu; Toshima, Hiroki; Inokuchi, Akihiro; Tanaka, Daisuke
Abstract : To realize lanthanide metal–organic frameworks (Ln-MOFs) with white light emission, it is necessary to adjust their RGB composition. We adopted the Bayesian optimization technique to optimize the stoichiometric ratio of metal-salts in Ln-MOFs. Abstract : To realize lanthanide metal–organic frameworks (Ln-MOFs) with white light emission, it is necessary to adjust their RGB composition. We adopted the Bayesian optimization technique to optimize the stoichiometric ratio of metal-salts in Ln-MOFs. We successfully synthesized MIL-103 (Ln(BTB)(H2 O), H3 BTB = 1, 3, 5-tris(4-carboxyphenyl)benzene), which emits white light.